The Impact of Working Capital Management on Profitability: The Case of Small and Medium-Sized Export Companies in Tunisia - Bellouma, Meryem (Management international / International Management / Gestiòn Internacional, 2011)
Working capital is an important component in the financial decision of the company. An optimal working capital management is reached through a trade off between profitability and liquidity. This study aims to provide empirical evidence about the effects of working capital management on the profitability of 386 Tunisian export SMEs observed from 2001 to 2008.The results of fixed and random effects models show a negative relationship between corporate profitability and the different working capital components. This reveals that Tunisian export SMEs should shorten their cash conversion cycle by reducing the number of days of accounts receivable and inventories to increase their profitability.